Mechanisms for metastable phase transformations in Co-Si and Fe-Co alloys - Baker, Evan. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Anil Saigal, Peggy Cebe, and Jonghyun Lee.; Keywords: Materials Science, and Mechanical engineering.